2021
DOI: 10.1016/j.ipej.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine and QTc prolongation in patients with COVID-19: A systematic review and meta-analysis

Abstract: Background Among many drugs that hold potential in COVID-19 pandemic, chloroquine (CQ), and its derivative hydroxychloroquine (HCQ) have generated unusual interest. With increasing usage, there has been growing concern about the prolongation of QTc interval and Torsades de Pointes (TdP) with HCQ, especially in combination with azithromycin. Aims This meta-analysis is planned to study the risk of QTc prolongation and Torsades de pointes (TdP) by a well-defined criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The results of clinical trials points to its use in supportive care treatment and it is administered alone or in combination with hydroxychloroquine [ 73 , 74 ]. However, there are recent reports of QT interval prolongation caused by azithromycin and hydroxychloroquine administration in COVID-19 patients [ 75 ], with prevalence showed in a meta-analysis of 13 studies involving 2138 patients [ 76 ].…”
Section: Drug-induced Hepatic Injury In Covid-19mentioning
confidence: 99%
“…The results of clinical trials points to its use in supportive care treatment and it is administered alone or in combination with hydroxychloroquine [ 73 , 74 ]. However, there are recent reports of QT interval prolongation caused by azithromycin and hydroxychloroquine administration in COVID-19 patients [ 75 ], with prevalence showed in a meta-analysis of 13 studies involving 2138 patients [ 76 ].…”
Section: Drug-induced Hepatic Injury In Covid-19mentioning
confidence: 99%
“…The results of clinical trials points to its use in supportive care treatment and it is administered alone or in combination with hydroxychloroquine [99,100]. However, there are recent reports of QT interval prolongation caused by azithromycin and hydroxychloroquine administration in COVID-19 patients [101], with prevalence showed in a meta-analysis of 13 studies involving 2,138 patients [102].…”
Section: Azithromycinmentioning
confidence: 99%
“…The surprising result was the insignificant association between QT interval prolongation and the use of HCQ. It was difficult to find a study that supported our result, as most studies showed frequent prolongation of the QT segment (45). Our result can be explained by the local protocol used in our hospitals.…”
Section: Discussionmentioning
confidence: 58%